Search for heavy neutrinos and right-handed W bosons in events with two leptons and jets in pp collisions at √ s =7 TeV with the ATLAS detector - Anduaga, Xabier Sebastián (2012)
This letter reports on a search for hypothetical heavy neutrinos, N, and right-handed gauge bosons, WR, in events with high transverse momentum objects which include two reconstructed leptons and at least one hadronic jet. The results were obtained from data corresponding to an integrated luminosity of 2.1 fb−1 collected in proton–proton collisions at √ s = 7 TeV with the ATLAS detector at the CERN Large Hadron Collider. No excess above the Standard Model background expectation is observed. Excluded mass regions forMajorana and Dirac neutrinos are presented using two approaches for interactions that violate lepton and lepton-flavor numbers. One approach uses an effective operator framework, the other approach is guided by the Left– Right Symmetric Model. The results described in this letter represent the most stringent limits to date on the masses of heavy neutrinos and WR bosons obtained in direct searches.